2015
DOI: 10.5812/aapm28056
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized and Saline Solutions in the Maintenance of Arterial and Central Venous Catheters After Cardiac Surgery

Abstract: Background:Heparinized saline solution is used to prevent occlusion in the arterial catheters and central venous pressure monitoring catheters. Even at low dose, heparin administration can be associated with serious complications. Normal saline solution can maintain patency of arterial catheters and central venous pressure monitoring catheters.Objectives:The current study aimed to compare the efficacy of normal saline with that of heparinized one to maintain patency of arterial and central venous catheters aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
1
20
0
7
Order By: Relevance
“…Thus, a total of 10 studies were eligible according to the inclusion criteria. The 10 studies were from Germany [13] ( n  = 1), Spain [6] ( n  = 1), Belgium [26] ( n  = 1), Italy [27] ( n  = 1), Japan [28] ( n  = 1), Iran [29, 30] ( n  = 2) and the USA [2, 31, 32] ( n  = 3). As a result, the 10 trials, including four ICU and six non-ICU studies, were reported in the years 2002–2015 and the average duration of follow up ranged from 1 to 400 days.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a total of 10 studies were eligible according to the inclusion criteria. The 10 studies were from Germany [13] ( n  = 1), Spain [6] ( n  = 1), Belgium [26] ( n  = 1), Italy [27] ( n  = 1), Japan [28] ( n  = 1), Iran [29, 30] ( n  = 2) and the USA [2, 31, 32] ( n  = 3). As a result, the 10 trials, including four ICU and six non-ICU studies, were reported in the years 2002–2015 and the average duration of follow up ranged from 1 to 400 days.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the COVID-19 outbreak, a number of studies have examined the use of LDHS protocols in ICU patients to improve a-line patency, with mixed results [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , 25 , 26 ]. The proposed mechanism of the LDHS protocol is infusing the anticoagulant directly to the site of potential clot formation proximal to the catheter tip.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes are mixed on the success of similar LDHS protocols implemented to improve a-line duration in non-COVID-19 patients. While some randomized-controlled trials report improved a-line patency in medical ICU and pediatric patients [ [6] , [7] , [8] ], several studies found no clinical effect [ [9] , [10] , [11] , [12] ], and these protocols have not been widely implemented. Study populations and dosages varied between studies, and thus it was unclear whether an LDHS protocol would benefit critically ill patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the overwhelming evidence in human patients showing that 0.9% sodium chloride is an effective flushing solution to maintain CVC patency (Bradford et al 2015;Bradford et al 2016a;Bradford et al 2016b;Heidari Gorji et al 2015;LeDuc 1997;Ziyaeifard et al 2015), heparinized saline is still used in many veterinary facilities (Fleeman 2001). Based on the results of the present study, 0.9% sodium chloride appears to be a safe alternative to heparin for flushing CVCs and may prove to be more cost effective for facilities, saving both time and money (Ridyard et al 2017).…”
Section: Discussionmentioning
confidence: 99%